Rethinking Muhammadiyah: Masjid, Teologi Dakwah Dan Tauhid Sosial (Perspektif Filsafat Dakwah) - Robby H. Abror (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
As a dakwah movement that has a social ideals to bring the genuine Islamic community is the basic philosophical of Muhammadiyah’s movement. There are three important concepts such as, the movement of jama’a, qaryah tayyibah and sakinah family. Then came the strategy of